ANALISIS HUKUM TERHADAP PELAKSANAAN PERLINDUNGAN DATA PRIBADI PASIEN DALAM SISTEM REKAM MEDIS ELEKTRONIK - Aprilia Fadila Nasir; Edi Pranoto (Universitas Katolik Santo Thomas Medan, 2025)
The digital transformation of the healthcare sector presents significant challenges to the protection of patients personal data, particularly in the implementation of Electronic Medical Records (EMR) systems. This study seeks to analyze the legal safeguards afforded to patients personal data within EMR systems at two hospitals in Semarang City, namely RSD KRMT Wongsonegoro and RSI Sultan Agung. Employing a juridical-empirical approach, the research examines national legal frameworks such as Law No. 27 of 2022 on Personal Data Protection and Law No. 17 of 2023 on Health and relates them to internal hospital policies and practices. The findings indicate that both hospitals manage their EMR systems independently, implement data backup mechanisms, restrict access to data through user-specific accounts, and provide regular staff training. While these measures generally comply with applicable legal provisions, challenges persist, including the risk of data breaches caused by physical disasters and infrastructure limitations. Consequently, there is a pressing need to strengthen information security systems and continuously enhance human resource capacity. Overall, this study underscores the importance of synergy among regulation, technology, and professional ethics in ensuring the effective protection of patients personal data.